Molluscs Combing on The Coast of Karang Hawu, West Java - Bunjamin Dharma (Jurnal Moluska Indonesia, 2020)
Karang Hawu Beach faces the Indian Ocean, so the presence of mollusks in the area varies widely and can increase in variety due to natural phenomena, such as earthquakes and tsunami outbreaks. The research objective was to obtain gastropods and bivalves (mollusks) by sweeping the Karang Hawu beach, West Java. Samples were collected from the coastal waters of Karang Hawu, West Java using the coastal sweeping method, then the samples were identified. The results showed that there were 3 classes of mollusks, namely: Cephalopod class, Bivalvia class, and Gastropod class with 42 families and 146 species of mollusks. Mollusks, with the highest gastropod class (38 families, 140 species), Bilavia class (3 families, 5 species), and Cephalopod class (1 family, 1 species). Results of the study concluded that based on the Molluscs sweeping the coast of Karang Hawu, West Java, it has a diversity of Molluscs, namely 146 species of mollusks from 3 classes, which were Gastropods, Bivalves, and Cephalopods.